Power applications for fuel-cell using switching regulators - Dega Rajaji Vanka; K. Chandra Sekhar (Institute of Advanced Engineering and Science, 2019)
Generally the switch mode power supply input voltage source is constant or shows insignificant little varieties.in any case, when fuel call used input source the last assumption is not valid. A fuel cell stack is give a details of low and not controlled DC output voltage, moreover, when the demanded current increases the output voltage becomes low in a nonlinear form; from now on, suitable controller is required to taken the previously mentioned issues. In this article, a normal current-mode controller is planned to using a joined model for an energy unit stack and a boost converter; besides, the resolving control method increasing the system stability and output voltage regulation.. The proposed energy system utilizes an energy component power (polymer electrolyte film fuel cell) and a boost converter passing on power of 900 W. the proposed controller execution for output voltage regulation by means of closed loop gain estimations and step load changes. What's more, a correlation amongst open-and closed- loop estimations is made, where the controller robustness is tried for vast load varieties and fuel cell stack output voltage changes are shows on simulation results.